Becoming a decision-making supporter for someone with acquired cognitive disability following traumatic brain injury. Issue 1 (2nd January 2016) - Knox, Lucy; Douglas, Jacinta M.; Bigby, Christine
Abstract : Despite an increased awareness of society's obligation to ensure that people with cognitive disabilities have access to decision-making support, little is known about how this support should be provided. For people with traumatic brain injury, informal support mechanisms may provide the primary means of support but there is limited understanding of how this aids participation. As part of a larger project using constructivist grounded theory to explore processes used by adults with severe traumatic brain injury in making decisions after injury, the authors explored a single-case study, presented in this article. In particular, the study aimed to build an understanding of the evolution of decision-making support over time from multiple perspectives. Data consisted of seven in-depth, individual interviews with three participants: the central participant, Beau, and two participants whom he nominated as his decision-making supporters. Analysis of the data revealed several key themes relating to both the nature of the decision-making process and the factors that underpinned decision-making support. Relational factors included: (a) knowing who I am and what I value; (b) understanding the nature of the relationship; and (c) working with each other. Process factors included: (a) sharing a vision; (b) adjusting process to decisional circumstances; and (c) developing a supportive network. Findings emphasised that knowing the person well and sharing a focus on maximising autonomy contributed to positive decision-making support. However, the data also highlight potential challenges associated with the role of decision-making supporter and the importance of support for those who take on this role.